2005
DOI: 10.1007/s00535-005-1609-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective A2A adenosine agonist ATL-146e attenuates acute lethal liver injury in mice

Abstract: The present findings suggest that the highly selective adenosine A2A receptor agonist (ATL-146e) prevents endotoxin-induced lethal liver injury by suppression of TNF-alpha secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…In liver injury, alterations in cytokine release, fatty acid metabolism, acute toxic liver injury, ischemia-reperfusion damage, and toxininduced liver fibrosis are modulated by adenosine. Adenosine effects cell changes via signaling through its four G proteincoupled receptors: A 1 , A 2a , A 2b , and A 3 (5,30,(33)(34)(35)43). Of particular relevance to the present study, adenosine regulates a number of fibrogenic functions in myofibroblastic HSC.…”
Section: Discussionmentioning
confidence: 82%
“…In liver injury, alterations in cytokine release, fatty acid metabolism, acute toxic liver injury, ischemia-reperfusion damage, and toxininduced liver fibrosis are modulated by adenosine. Adenosine effects cell changes via signaling through its four G proteincoupled receptors: A 1 , A 2a , A 2b , and A 3 (5,30,(33)(34)(35)43). Of particular relevance to the present study, adenosine regulates a number of fibrogenic functions in myofibroblastic HSC.…”
Section: Discussionmentioning
confidence: 82%
“…as regeneration [45], injury [46,47], ischemia/reperfusion [48], and fibrosis [10]. Thus, it is scientifically worthwhile to clarify the cell-specific distribution of the various purinergic signaling components expressed in the liver tissue.…”
Section: Ecto-nucleotidasesmentioning
confidence: 99%
“…[29][30][31] Ohta, Sitkovsky and others showed that, among the different adenosine receptors (A1, A2A, A2B and A3), 26 the adenosine receptor 2A has a major role in the attenuation of inflammation and tissue damage. 20,21,[32][33][34][35] These studies evidenced the CD39-CD73-adenosine receptor axis blockade as a promising therapeutic target. 31,[36][37][38][39][40][41][42] In line with these studies and with the objective to better understand the mechanism involved in the acquisition by TAM of an immunoregulatory phenotype, this study aimed at evaluating the impact of ATP and ATP metabolites on TAM functions.…”
Section: Introductionmentioning
confidence: 99%